2018
DOI: 10.1039/c8ra06295a
|View full text |Cite
|
Sign up to set email alerts
|

A novel surface plasmon resonance sensor based on a functionalized graphene oxide/molecular-imprinted polymer composite for chiral recognition of l-tryptophan

Abstract: Novel SPR sensor for chiral recognition of l-tryptophan using a functionalized graphene oxide/molecularly-imprinted polymer composite as a recognition element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 40 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Among the existing optical techniques to detect Hg 2+ are colorimetric, fluorescent, chemosensor, electrochemiluminescence (ECL) and photoluminescent (PL) [32][33][34]. Though these techniques are widely used, they encounter from many drawbacks, such as high instrument operating costs, repetitive pretreatment procedures and long initiation times [35].…”
Section: Introductionmentioning
confidence: 99%
“…Among the existing optical techniques to detect Hg 2+ are colorimetric, fluorescent, chemosensor, electrochemiluminescence (ECL) and photoluminescent (PL) [32][33][34]. Though these techniques are widely used, they encounter from many drawbacks, such as high instrument operating costs, repetitive pretreatment procedures and long initiation times [35].…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al demonstrated a surface plasmon resonance (SPR) sensor on a molecular-imprinted polymer functionalized/ composite graphene oxide (GO) for the chiral recognition of L-Trp. 32 The recognition element of the composite was arranged via a green synthesis methodology using polydopamine as a functional monomer, a reducer and a cross-linker for molecular imprinting. The SPR chip's gold surface was used to attach the composite and contact-angle measurements were carried out to characterize the sensor.…”
Section: Miscellaneous Pathwaysmentioning
confidence: 99%
“…SPR sensors have mostly been used for sensing in the liquid phase in the situation of enantiomeric discrimination. Using a functionalized GO‐MIP composite as a recognition element, Xu and coworkers created a new SPR sensor for the chiral recognition of L‐Trp [310]. The composite was easily made using novel mussel‐inspired surface chemistry based on DA oxidative polymerization.…”
Section: Chiral Resolution Np Sensing Approachesmentioning
confidence: 99%